(untitled) (AYUSHDHARA, 2025)
Fifty categories of Mahakashayas have been outlined, along with five hundred specific examples, to illustrate their therapeutic applications, acknowledging the infinite scope of medicinal formulations. The concise presentation aims to provide a foundational understanding for practitioners with limited cognitive capacity while serving as a reference framework for advanced practitioners to foster further intellectual exploration and innovation in treatment methodologies. This article is being developed from an innovation perspective and aims to explore how contemporary research methodologies can be applied to investigate the anticancer properties of drugs categorised under Vishaghna Mahakashaya which are Haridra (Curcuma longa), Manjishtha (Rubia cordifolia), Suvahaa (Operculina turpethum), Sukshama Ela (Elettaria cardamomum), Paalindee (Hemidesmüs indicus), Chandan (Santalum album), Kataka (Strychnos potatorum), Shirish (Albizia lebbeck), Sinduvaara (Vitex negundo) and Shleshmaataka (Cordia dichotoma) contributing to cancer care and prevention. Ayurvedic interventions are not proposed as replacements for conventional allopathic cancer treatments but rather as complementary approaches to support prevention, enhance resilience, and restore immune function.